Arylamine N-Acetyltransferases from mycobacteria: investigations of a potential yarget for anti-tubercular therapy - Abuhammad, A (2013)
Reactivation of latent infection is the major cause of tuberculosis (TB). Cholesterol is a critical carbon source during latent infection. Catabolism of cholesterol contributes to the pool of propionyl-CoA, a precursor that is incorporated into cell-wall lipids. Arylamine N-acetyltransferase (NAT) is encoded within a gene cluster that is involved in the sterol-ring degradation and is essential for intracellular survival. NAT from M. tuberculosis (TBNAT) can utilise propionyl-CoA and therefore was proposed as a target for TB-drug development. Deleting the nat gene or inhibiting the NAT enzyme prevents intracellular survival and results in depletion of cell-wall lipids. NAT inhibitors, including the piperidinol class, were identified by high-throughput screening. The insolubility of recombinant TBNAT has been a major limitation in pursuing it as a drug target. Subcloning tbnat into a pVLT31 vector resulted in a yield of 6-16 mg/litre-bacterial-culture of pure-soluble recombinant TBNAT. The increased yield allowed for extensive screening for crystallisation conditions. However, since a structure was not obtained, the model NAT from M. marinum (MMNAT) was employed to further understand NAT as a target. Screening against a panel of Acyl-CoA cofactors showed that MMNAT can also utilise propionyl-CoA. The MMNAT structure in complex with the high affinity substrate hydralazine was determined (2.1 Å) and the architecture of the arylamine pocket was delineated. A novel mechanism for the acetylation reaction of hydralazine has emerged. It is proposed that the acetyl group is transferred from acetyl-CoA to the heterocyclic aromatic nitrogen of hydralazine, which explains the immediate cyclisation of the acetylated metabolite into an N-methyltriazolophthalazine. By employing mass spectroscopy, enzyme assays, computational docking and structural studies, a covalent mechanism of inhibition by the piperidinol class was established, and the inhibitor-binding pocket was identified. Inhibitors with new scaffolds were identified using the in silico 3D-shape screening and thermal shift assay.